Circadian rhythms identified in Caenorhabditis elegans by in vivo long-term monitoring of a bioluminescent reporter - Goya, María Eugenia (2016)
Circadian rhythms are based on endogenous clocks that allow organisms to adjust their physiology and behavior by entrainment to the solar day and, in turn, to select the optimal times for most biological variables. Diverse model systems - including mice, flies, fungi, plants, and bacteria - have provided important insights into the mechanisms of circadian rhythmicity. However, the general principles that govern the circadian clock of Caenorhabditis elegans have remained largely elusive. Here we report robust molecular circadian rhythms in C. elegans recorded with a bioluminescence assay in vivo and demonstrate the main features of the circadian system of the nematode. By constructing a luciferase-based reporter coupled to the promoter of the suppressor of activated let-60 Ras (sur-5) gene, we show in both population and single-nematode assays that C. elegans expresses ∼24-h rhythms that can be entrained by light/dark and temperature cycles. We provide evidence that these rhythms are temperature-compensated and can be re-entrained after phase changes of the synchronizing agents. In addition, we demonstrate that light and temperature sensing requires the photoreceptors LITE and GUR-3, and the cyclic nucleotide-gated channel subunit TAX-2. Our results shed light on C. elegans circadian biology and demonstrate evolutionarily conserved features in the circadian system of the nematode.